1999
DOI: 10.1152/ajpendo.1999.277.5.e792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in plasma melatonin in sheep is due to pineal weight, not to variations in enzyme activities

Abstract: This study was conducted to determine the origin of the high variability in the mean nocturnal plasma melatonin concentration (MC) in sheep. Two extreme groups of 25 lambs each [low (L) and high (H)] were obtained by calculating their genetic value on the basis of the MC of their parents. The MC of lambs was significantly higher in the H group than in the L group (L: 189.7 +/- 24.4 vs. H: 344.1 +/- 33.0 pg/ml, P < 0.001). Within each group, 13 lambs were slaughtered during the day (D) and 12 lambs during the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 11 publications
1
28
1
2
Order By: Relevance
“…By referring to the multiple and step-to-step regression analyses, we can assume that the variation in the number of pinealocytes may explain about 80%, and the volume of pinealocytes about 20%, of the total variation in pineal weight. Thus, the difference between the two genetic groups of extreme lambs regarding their pineal weight at slaughter, already found in a previous experiment (Coon et al 1999), originated from a higher multiplication rate of pinealocytes rather than an enlargement of the same number of cells. This difference in number of pinealocytes was observed at slaughter, at 14 weeks old.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…By referring to the multiple and step-to-step regression analyses, we can assume that the variation in the number of pinealocytes may explain about 80%, and the volume of pinealocytes about 20%, of the total variation in pineal weight. Thus, the difference between the two genetic groups of extreme lambs regarding their pineal weight at slaughter, already found in a previous experiment (Coon et al 1999), originated from a higher multiplication rate of pinealocytes rather than an enlargement of the same number of cells. This difference in number of pinealocytes was observed at slaughter, at 14 weeks old.…”
Section: Discussionmentioning
confidence: 60%
“…While the physiological significance of this genetic variability in melatonin secretion is unknown, investigations conducted regarding their physiological origin have demonstrated that such a variability comes from differences in the synthesis of melatonin from the pineal gland (Zarazaga et al 1998b). More specifically, this ability of the pineal gland is not related to enzymatic activity per mg of tissue, but to the size of the pineal gland, which can vary from 30 mg to more than 200 mg (Coon et al 1999). However, despite a well-established characterization of 'high secretors' and 'low secretors' of melatonin in adult sheep, we do not know whether this is due to differences in the number, or in the size, of pinealocytes in the pineal gland.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-rat A ANAT 22-37 pT31 (As 3352), antioAANAT (As 3343), and anti-oAANAT (As 2819, also referred to as anti-AANAT 1-205 ) have been described (4,17,18). Antisera were immunopurified (19) by using synthetic phosphopeptide (As 3352, As 5901), unphosphorylated peptide (As 3343), or unphosphorylated protein (As 2819).…”
Section: Phosphorylation Of Expressed Andmentioning
confidence: 99%
“…5, which is published as supporting information on the PNAS web site) and does not detect unphosphorylated AANAT, oAANAT T31A S205G, or AANAAT pT31 S205A. Immunopurified anti-rat AANAT 22- (18). Additional details appear in the figure legends.…”
Section: Phosphorylation Of Expressed Andmentioning
confidence: 99%
“…Mesurées dans le sang de la veine jugulaire, elles varient, dans l'espèce ovine, de moins de 50 pg/ml à 1000 pg/ml (Zarazaga et al 1998). Cette variabilité inter-individuelle, répétable et héritable, n'est pas due à des variations de l'activité des enzymes de synthèse de la MLT mais à la taille de la glande pinéale et au nombre de pinéalo-cytes qu'elle contient (Coon et al 1999). Les concentrations de MLT sont trois à cinq fois inférieures dans les artères caro-tides à celles constatées dans les veines jugulaires.…”
Section: La Mélatonine Est Présente En Fortes Concentrations Dans Le Lcrunclassified